Composición y abundancia de aves rapaces diurnas en los alrededores de la ciudad de Iquitos, Loreto-Perú.2020 - Paredes Soplín, James Paul (2021)
From august to november 2020, I carry out observations about of the composition and abundance of birds daytime raptors in surroundings of the Iquitos city (Perú), by lineal transect and boat census. Birds daytime raptors has conformed by Accipitriformes and Falconiformes, with 3 families (Pandionidae, Accipitridae y Falconidae) and specific richness the 13 species. Milvago chimachima reported a density what various between 6.25 to 43.80 ind/km2 duraning the months of sampling, and others birds low densities. I concludes what the composition of birds daytime raptors in surrounds of Iquitos city, has conformed by a specific richness of 13 especies (Accipitriformes y Falconiformes) and densities low in most the species.